Podręczny słownik przezroczystości - Misun, Jakub (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article discusses an essay collection by Marek Bieńczyk, Przeźroczystość [Transparency]. The concept, placed in various context, shows various aspects and is seen in various shades. The author does not put forward a statement, but rather proposes a work to be done: to determine the modality of transparency. The concept initially seems to be mainly epistemological: the cognizant subject would like to make the world transparent, to discover all possible mysteries. Before that, however, the subject must know itself, and here the dream of transparency also plays the key role. Lack of epistemological transparency is the main cause of melancholy and its reverse — hysteria. The concept turns out to be important in the domain of love — the loer thinks that (s)he knows the desired person more better anybody else, that (s)he has entirely penetrated the subjectivity of the Other. Ultimately, however, the dream of transparency goes down to a slow demise of the subject: as self-discovery progresses, there is less and less of the discoverer. In conclusion of this work, the border of modality of the concept turns out to be horrifyingly obvious. The desire for transparency consequently searches not for knowledge, but for an escape whose name is death.